CORRELATION BETWEEN DOG OWNER KNOWLEDGE AND THE ROLE OF HEALTH WORKERS IN PREVENTING RABIES IN AMBON CITY - Pollan Versilia Wuritimur; Dwi Sutiningsih; Bagoes Widjanarko (Jurnal Berkala Epidemiologi, 2020)
Background: Rabies is a zoonotic disease that can cause death. Ambon City is a city in Indonesia with a fairly high dog population of 62,613; we found 3,444 bite cases and 747 positive results from dog brain specimens between 2014 and 2018. Purpose: The aim of this study was to examine the correlation between the knowledge of dog owners and the role of health workers in preventing rabies in Ambon City. Method: This research used a quantitative design within a cross-sectional study. There were two groups of respondents: the dog owner population and the health worker population. The population of dog owners was 4,509 and the sample was 113. The health worker population and sample size was 22. The research began with the preparation, implementation, and writing stages. The data sources were both primary and secondary. Primary data were obtained at the time of the study and secondary data were obtained from the Ambon City Health Office, Ambon City Agriculture and Food Security Service, and Ambon City Health Centers. Results: There was a relationship of statistical significance between dog owner knowledge and rabies prevention (p = 0.01) and a significant relationship between the role of health workers and rabies prevention (p = 0.03). Conclusion: Dog owner knowledge and the role of health workers have a relationship with efforts to prevent rabies.